Susan B. Anthony : A Biography - Barry, Kathleen (New York University Press, 2020)
Brings to life one of the most significant figures in the crusade for women's rights in AmericaThis comprehensive biography of Susan B. Anthony traces the life of a feminist icon, bringing new depth to our understanding of her influence on the course of women's history. Beginning with her humble Quaker beginnings in rural Massachusetts, to her late twenties when she left her secure teaching position to become a politician--and a champion of women's rights--this book offers an in-depth look at the ways Anthony's life experiences shaped who she would become. Drawing on countless letters, diaries, and other documents, Kathleen Barry offers new interpretations of Anthony's relationship with feminist Elizabeth Cady Stanton, and illuminating insights on Anthony's views of men, marriage, and children. She paints a vivid picture of the political, economic, and cultural milieu of 19th-century America. And, above all, she brings a very real Susan B. Anthony to life. Here we find a powerful portrait of this most singular woman--who she was, what she felt, and how she thought.Complete with a new preface to honor the 100th anniversary of women's suffrage and Anthony's vital role in the fight for voting rights, this thorough biography gives us essential new insight into the life and legacy of an enduring American heroine.